What Kind of Critique for Central and Eastern European Legal Studies? Comparison as One of the Answers - Mercescu, Alexandra (Acta Universitatis Lodziensis. Folia Iuridica, 2019)
This paper seeks to emphasize the merits of comparative law as a critical legal enterprise. For this purpose, it first provides a brief overview of the various forms of critique that have been advocated in the field of comparative law. Second, it discusses four epistemological concerns as regards legal comparison that are meant to orient comparatists towards a critical mode of comparative reasoning. While most of the remarks comprised in this contribution apply to legal comparisons in general, a few observations shall be made with specific reference to the stakes and limits of legal comparisons in Central and Eastern Europe.